Shared Identity and Trust Among the Furry Fandom: A Narrative Review - Amarta, Rifqi Zuhdi; Kartika, Dilah Ratna (Universitas Gadjah Mada, 2024)
Shared identity has played a major role in the formation of fandom in the digital age, where online interaction became the dominating mode of social interaction among individuals. The Furry fandom's online ingroup interactions are examined through the evolving process of identity and trust development, highlighting the role of virtual platforms in fostering community cohesion. This paper reviews previous literature about Furry fandom from four aspects of Social Exchange Theory (SET), namely trust, commitment, reciprocity, and power. The narrative review method is employed to explore how these aspects contribute to the resilience of shared identity and trusts within the Furry fandom. The review conducted on six scholarly articles surrounding the theme of Furry ingroup interaction underlined a common belief in how individuals who identify as Furry share a common sense of identity, which fosters a sense of trust and camaraderie within the community. This shared identity serves as a foundation for a sustainable ingroup trust and contributes to the overall cohesion of the furry fandom. This paper suggests that future research could adopt a more in-depth analysis on the importance of trust and its sustainment within ingroup interaction in the scope of the digital age.